Konsep “Kesetaraan Iman dan Perbuatan” Dalam Teologi Neo Evangekalisme Ditinjau Dari Perspektif Teologi Paulus Dalam Surat Roma 5:1b - Laos, Tonny (JURNAL ILUMINASI, 2026)
In Christianity, fat and deeds hold equel value. In this regerd, Evangelicalism emphasizes tha importance of social deeds over faith as a tangible expression of faith, a means of introducing the Gospel, and proof of love others and God. The method employed in this study is the hermeneutical approach developed by Grant Osborne, focusing specifically on faith as discussed in Romans 5:1a, and responding to the Evangelical understanding that compares faith with deeds. The research findings indicate that humanity is justified by faith in Jesus Christ, not by sosial deeds. This clarifies that deeds are te fruit or result of faith that has already been obtained. While social deeds can be performed by anyone, faith, acquired belief in Christ, is not possessed by everyone, meaning social deeds cannot be used as a measure to convey the Gospel (faith in Christ) to those who do not yet know Christ. True faith will lead a person to live righteously and produce results in their deeds, in accordance with God’s will.